Tecnologias educacionais: Estratégias de formação de professores para uso de TIC na ETI Olga Benário – Palmas - TO - Rodrigues, Raimundo Ferreira (Universidade Federal do Tocantins, 2021)
This research deals with the use of technologies in the educational context, notably on teacher training strategies for the use of Information and Communication Technologies in a school in Palmas - Tocantins. The main objective was to identify the contributions of the educational strategies of the use of ICT for the improvement of the teachers of the researched institution. The main objective was to identify the contributions of the educational strategies of the use of ICT for the improvement of the teachers of the researched institution. The research problem, what are the contributions of the educational strategies of ICT use to the improvement of the teachers of the field school. From the study it was found that the school faces challenges pertinent to the lack of public policies aimed at continuing education, discontinuation of in-service training and few technological resources available at school, being insufficient for the demand in the institution and in view of the need for its adaptation to the contemporary technological context. The recurring obstacles make it difficult for the teacher to rise in his career. We seek to contribute to teacher training in service and through strategic actions developed with the participation of professionals of the institution in search of improvements in training. The methodology used was the action research methodology, through problem identification, action planning, joint action, evaluation of the results of actions developed and monitored from training activities, workshops and classes. Taught by the school's professionals. The main conclusions point out that the teacher tries to build a solid teaching identity that is coherent with the knowledge and information society, but is deprived of support or minimal training, offered in a discontinuous way, without value in career hours, or even for not having time for studies or being able to afford continuing education. There is a need for investment in public policies for the continuing education of teachers as they go through constant setbacks and challenges and unfold in search of materials and methods favorable to their performance in daily school life. The actions developed with the professionals served to train teachers, encourage them to continue seeking career improvements, optimized their classes using their personal technologies and those available to the school, overcame part of the difficulties faced and were willing to continue seeking improvements to the process. Teaching-learning.